Benefícios do treinamento físico para pessoas vivendo com HIV - Pedro, Rafael Evangelista (2016)
Life expectance of people living with HIV/aids is increasing due mainly the advances in its treatment, which decreases the number of complications related to virus. However, the treatment has been associated with several side effects, which in general has been increasing the risk of development of cardiovascular diseases (CVD) and the number of deaths related to metabolic diseases and cardiac events. In light of, physical training has been a strategy to improve the co-morbidities related to HIV and its treatment; however, the benefits of physical training to these people are incipient yet. Therefore, the aims of this study were: 1) to verify the effects of concurrent physical training on cardiorespiratory fitness, muscle strength, and resting heart rate variability (HRVrest) of HIV-infected people; 2) systematically to review the literature about the effects of physical training on physical fitness, quality of life, body composition, lipid profile, and inflammatory markers in HIV-associated lipodystrophy syndrome (HALS); 3) to compare the benefits of concurrent physical training on peak velocity (Vpeak), muscle strength, body composition, lipid profile, blood glucose, adiponectin, leptin and C-reactive protein levels, and HRVrest between HIV-infected and -non-infected people. In the first study 43 HIV-infected people were divided in two groups; 25 were enrolled, thrice a week, in a concurrent training program for 16 weeks and 18 assigned to the control group. There were improvements in peak oxygen uptake (VO2peak), Vpeak, muscle strength, and in some HRVrest indices in response to concurrent training. In the second study, five studies were qualitatively analyzed; the results have shown that physical training improves cardiorespiratory fitness and muscle strength, there are indicatives of improvements in plasma inflammatory markers; however, there is no consensus about the effects on body composition and lipid profile in people with HALS. In the third study 42 people have undergone a 10-week concurrent training program, three times per week: 18 HIV-infected and 24 non-infected. It was shown that both groups increased Vpeak and muscle strength. It was also shown that both groups improved some HRVrest indices and increased HDL concentrations; notwithstanding, the HIV-infected people remain with HDL levels lower than HIV-non-infected people. There were not improvements in body composition and in plasma adiponectin, leptin, and C-reactive protein. In general, it is conceivable to conclude that physical training improves physical fitness, some HRVrest indices, and lipid profile in the same way between people living with HIV/aids and HIV-non-infected people.